Controlling Dentistry-Related Musculoskeletal Disorders with Ergonomic Interventions in Lahore, Pakistan - Nasar, Marriyam; Rubab, Farwa; Shahzad, Hazik Bin; Qureshi, Minam; Shahid, Maham; Batool, Pakiza (Makara Journal of Health Research, 2021)
Background: Musculoskeletal disorders (MSDs) usually result from a prolonged static position and repetitive movements. A comfortable environment, appropriate working position, and multiple short breaks could alleviate MSDs. While the occasional back or neck ache is not a cause for alarm, regularly occurring pain or discomfort, if ignored, may further develop into an injury or career-ending disability. Methods: A total of 370 dentists were selected from two dental hospitals and multiple dental clinics in Lahore, Pakistan. Current MSDs were recorded with the Standardized Nordic Questionnaire (SNQ). Information sheets containing dental ergonomics and back and tendon-gliding exercises were distributed among the participants. The SNQ questionnaire was repeated after a 3-month interval. Results: MSDs were found to be present in 59.5% of the clinicians surveyed. Males dentists were significantly more prone to MSDs than female ones (p <0.001), and senior dentists had significantly fewer MSDs than younger dentists. The intervention of ergonomic guidelines and exercises led to a reduction in MSDs among dental clinicians, with neck pain being significantly reduced (p = 0.003). Conclusions: MSDs affect the clinical practice of dental surgeons. Thus, incorporating more detailed ergonomics at the undergraduate level, along with the wider dissemination of correct dental postures, techniques, stretching, and rest to dentists, should be emphasized.